Documentation Procedures for New Ship Contructions in The Shipbuilding Industry for Shipping Eligibility Certification Requirements at PT. Internusa Bahtera Batam - Bunga Rosa Amelya; Abdurohman; Iing Mustain, (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
In the shipping industry, documents and certifications are essential to ensure every ship meets safety and regulatory standards. For the shipbuilding industry, these documents are critical prerequisites for obtaining ship eligibility certifications. This study aims to analyze the procedures for fulfilling documentation requirements for new ship constructions in the context of shipping eligibility certification. This research employs a descriptive qualitative method, utilizing triangulated data collection through literature reviews, observations, and documentation. The study focuses on new ship constructions managed by PT Internusa Bahtera in Batam. The results reveal major challenges in the documentation process, including delays caused by incomplete submissions, lack of coordination among stakeholders, and technical issues in online systems. To address these challenges, the study recommends improving agent training, streamlining internal workflows, and enhancing technological systems to ensure efficiency and compliance with maritime standards. The procedural stages for new ships include tendering, contract formation, shipyard preparation, blueprint approval, keel laying, ship launching, ship measurement, and registration leading to certificate issuance. This research contributes to the shipping industry by providing insights and practical recommendations to improve the certification process, thereby supporting safer and more sustainable maritime operations.